2000
DOI: 10.1038/35002622
|View full text |Cite
|
Sign up to set email alerts
|

The LIM homeobox gene Lhx9 is essential for mouse gonad formation

Abstract: During mammalian embryonic development, the ovaries and testes develop from somatic cells of the urogenital ridges as indifferent gonads, harbouring primordial germ cells that have migrated there. After sex determination of the gonads, the testes produce testosterone and anti-Mullerian hormone which mediate male sexual differentiation, and the female developmental pathway ensues in their absence. Here we show that transcripts of the LIM homeobox gene Lhx9 are present in urogenital ridges of mice at embryonic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
258
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(279 citation statements)
references
References 19 publications
(34 reference statements)
7
258
0
2
Order By: Relevance
“…Null mutations in these genes prevent gonad formation in mouse embryos. (46)(47)(48) WT1 and SF1 have roles in subsequent testis development, participating in activation of the AMH gene. (49,50) Comparisons with the chicken system have shown that the expression profiles for these genes are highly conserved prior to sexual differentiation.…”
Section: Conserved Genes Within the Pathwaymentioning
confidence: 99%
“…Null mutations in these genes prevent gonad formation in mouse embryos. (46)(47)(48) WT1 and SF1 have roles in subsequent testis development, participating in activation of the AMH gene. (49,50) Comparisons with the chicken system have shown that the expression profiles for these genes are highly conserved prior to sexual differentiation.…”
Section: Conserved Genes Within the Pathwaymentioning
confidence: 99%
“…SF-1 is also an activator of the expression of enzymes involved in steroidogenesis, in particular aromatase (P450-arom), which catalyzes the conversion of androgens to estrogens (Lynch et al, 1993). Another factor implicated in gonadal morphogenesis is the LIM domain-containing homeobox factor Lhx9, of which deficiency leads to an arrest in gonad development before sex differentiation (Birk et al, 2000). DMRT1, another element of the testicular pathway, is a DM domain transcription factor whose inactivation leads to testis degeneracy, germ cell meiosis failure, and arrest in Sertoli cell differentiation in mice (Raymond et al, 2000) and to sex reversal in hemizygote XY humans (Raymond et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…In Lhx9 K/K mice, the gonad formation is arrested, and the proliferation of the epithelium into the mesenchyme is absent in Lhx9 K/K embryos (Birk et al 2000). In vitro biochemical experiments reveal that Lhx9 and Wt1 (KKTS) can directly bind to the Sf1 promoter and upregulate the expression of Sf1.…”
Section: Lim Homeoboxmentioning
confidence: 99%
“…Lhx9, a member of the LIM homeobox domain gene family, is initially expressed in the medial surface of the urogenital ridge at E9.5; and later is restricted to the mesothelial layer and the interstitial region at E13.5 (Birk et al 2000). In Lhx9 K/K mice, the gonad formation is arrested, and the proliferation of the epithelium into the mesenchyme is absent in Lhx9 K/K embryos (Birk et al 2000).…”
Section: Lim Homeoboxmentioning
confidence: 99%